The Public Service Loan Forgiveness Program and the Purpose of Higher Education - McKinnon-Crowley, Saralyn; Harris, Sarah A. (Critical Education, 2026)
This case study investigates the Public Service Loan Forgiveness Program (PSLF), a policy designed to enable student debt forgiveness after ten years of payments for individuals working in public service. The program has only forgiven a small number of loans; as of this writing less than 34% of people who have applied for the program have actually received loan forgiveness. What does this low number indicate about the program and the perception of higher education in the contemporary United States context? To answer that question, in this article, we review the history of the program, the scholarship about PSLF, and analyze its implementation using the tools of document analysis and critical policy analysis. We argue that the failure of the program communicates a clear message about the purpose of higher education in the United States under a neoliberal paradigm.